Seizures in Offspring of Epileptic Parents - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The risks Of unprovoked seizures in the offspring of parents with generalized versus partial epilepsies among 687 patients born in Rochester, MN between 1922 and 1985 and followed for the occurrence of seizures through 1986 are reported from the Division of Epidemiology and Department of Neurology, Columbia University, New York, the University of Texas Health Sciences Center, Houston, and the Section of Clinical Epidemiology, Mayo Clinic, Rochester, MN.